An experimental and theoretical study of the solidification process of phase change materials in a horizontal annular enclosure. (October 2019) - Gortych, M.; Lipnicki, Z.; Weigand, B.
Highlights: Phase change material solidification in a horizontal annular enclosure. The problem of liquid solidification in an annular enclosure under the influence of free convection. Determination of the heat transfer coefficient from the experimental data. The method of heat accumulation, based on the phase change phenomenon in the annular enclosure. Abstract: The main purpose of this paper is to examine experimentally and theoretically the process of heat accumulation and heat release for PCM ( phase change materials ) in an annular space. The theoretical part of this work provides a solution of the problem of liquid solidification in an annular space under the influence of free convection. Here a simplified quasi-steady-state model for solidification has been applied. The new simplified model describes the solidification phenomenon with an imposed boundary condition on the solidification interface by applying a heat transfer coefficient. From the developed model, the influence of various dimensionless parameters on the phase change problem can be seen clearly. Measurements and observation of the thickness of the solidified layer were performed in a newly built apparatus. In addition, this paper is also concerned with the role of the contact layer in the solidification process. Results are showing the thickness of the solidification layer depending on time and the distribution of the local heat transfer coefficient on the surface of the solidification front. The obtained experimental and numerical results show good agreement. The examined solidification process makes it possible to use the results obtained for the design of new heat accumulators. The presented method to analyse heat accumulation is important for power engineering. It opens up the possibility to reduce the size of heat accumulators, thus, possible leading to a reduction in their production costs.